LEGAL PERSPECTIVE ON AGRARIAN CONFLICT IN INDUSTRIAL DEVELOPMENT IN INDONESIA - Dikki Saputra Saragih; Micael Jeriko Damanik; Parlindungan Purba; Dewi Riama (PT. Radja Intercontinental Publishing, 2023)
Government policy in the industrial sector is considered 'failed' in industrialization in Indonesia because it ignores the culture of innovation and resource potential. Both rely on human problems as the main foundation of life. Experience in many countries where the industrialization process has always been successful proves that they always prioritize humans as the source and goal of the creation of industry itself. On the other hand, the function of law as a medium for industrialization in Indonesia cannot foster a culture of innovation because it only serves industrialized economic activities. The idea proposed to improve this case is to use two pillars, namely innovation culture and social structure, as the basis for industrialization planning and the function or use of law in economic development in Indonesia.